La fotografía como medio de difusión para la Prevención de Incendios Forestales en el cantón de Pelileo - Delgado Morales, Nelson Fernando (2025)
This project aims to use photography as a means of disseminating information to prevent forest fires in the canton of San Pedro de Pelileo, Tungurahua province, Ecuador. Through a mixed methodology that included surveys and interviews with students, farmers, and rural residents, the study explored the community's perceptions and knowledge about the issue and its prevention. The findings revealed insufficient dissemination of preventive information, alongside a strong community interest in participating in awareness strategies. The benchmarking analysis highlighted the need to strengthen the resources of the local Fire Department. The proposal includes a media plan designed to raise awareness among residents through impactful images that emphasize the importance of prevention and the protection of the natural environment. This project aims to promote fire prevention and environmental stewardship in the region, fostering a culture of responsibility and care for the local ecosystem